DETERMINANTS OF CUSTOMER SATISFACTION IN RETAIL BANKING: EMPIRICAL EVIDENCE FROM JAPANESE BANK CUSTOMERS - Mori, Yuji; Ozaki, Yasufumi; Harimaya, Kozo (Asian Finance & Banking Review, 2024)
As a consumer-oriented service industry, the quality of customer service provided by banks and their customers’ overall satisfaction with their services are becoming increasingly important. This study examines the factors influencing customer satisfaction with banking services provided by Japanese regional banks. Using data from the Japan Financial Institution Customer Ratings METER® of about 200,000 cases, we estimated the factors affecting customer satisfaction using an ordered probit model. The results indicate a positive correlation between direct financial services from regional banks and customer satisfaction. This relationship is solid when customers hold investment-related products. Additionally, we observed that individual customer satisfaction tends to decline with increasing financial asset holdings and increase as customers become more financially literate. Furthermore, we noticed that customer satisfaction tends to be higher for females than males, younger people than the elderly, and occupied customers than for unoccupied customers. The findings of this study suggest that customers may be more attracted to regional banks that provide investment information and advice tailored to their circumstances. It may be beneficial for regional banks to understand better factors that influence customer satisfaction, such as the age and gender of their customers, their level of financial Literacy, and the amount of financial assets they have. It would be beneficial for regional banks to consider these factors and enhance the quality of their direct interactions with customers and the customer service provided by their staff and call centers. This could help regional banks build long-term, ongoing relationships with their customers. JEL Classification Codes: G2, G20, G21.